The Effect of Lemongrass Stem (Cymbopogon citratus) and Salam Leaves (Syzygium polyanthum) Ethanol Extracts on The Number of Bactrocera Fruit Flies Catches - Yunisa Sucitra; Syamsul Bahri; I Putu Artayasa (Jurnal Biologi Tropis, 2022)
Bactrocera fruit fly (Diptera: Tephritidae) is one of the important pests in horticulture which is very detrimental. Lemongrass stems and salam leaves are be able used as vegetable attractants in controlling fruit fly pests. This study aimed to determine the effect of lemongrass (Cymbopogon citratus) and salam leaves (Syzygium polyanthum) ethanol extract and their mixtures on the number of catches of Bactrocera fruit flies and to determine the effect of the concentration of lemongrass (Cymbopogon citratus) and salam leaves (Syzygium polyanthum) ethanol extract and their mixtures on the number of catches of Bactrocera sp. The experimental design used in this research was a Randomized Block Design (RBD). The collected data were analyzed by F test two-way analysis at 95% significance level, followed by Honest Significant Difference Test (HSD) at 95% significance level. The results showed that the use of traps containing ethanol extracts of lemongrass stems and salam leaves and a mixture of the two had succeeded in catching two strains of fruit flies, namely Bactrocera albistrigata (97 individuals) and Bactrocera carambolae (32 individuals), while traps without these extracts failed to catch Bactrocera fruit flies. It is concluded the treatment of lemongrass stems (Cymbopogon citratus) and salam leaves (Syzygium polyanthum) ethanol extract, and their mixtures significantly effect on the number of Bactrocera fruit fly catches, while the treatment with different ethanol extract concentrations of 35%, 45%, and 55% has no significantly effect on the number of Bactrocera fruit fly catches.